Validasi Modul Elektronika Dasar Mengintegrasikan Creative Thinking Pada Materi Rangkaian Elektronika Yang Menggunakan Transistor dan Aplikasinya - Syahrani, Filda; Hufri, Hufri (Universitas Negeri Padang, 2020)
This research is based on the low creative thinking skills and the teaching materials used in the lessons have not facilitated the student to increase their creative thinking skill. The aims of this study was to determine the value of validity of basic electronics module integrates creative thinking in electronic circuit materials using transistor and application. The type of research used is research and development (R&D). The research procedure used in this study uses the ADDIE development model. The research steps include : analysis, design, development, implementation, evaluation. While the data analysis used is descriptive data analysis. Based on the data analyzed there are research results, namely the average value of validity of basic electronics module integrates creative thinking by experts with an average value of 86% and have very valid criteria. It can be concluded that basic electronics module integrates creative thinking in electronic circuit materials using transistor and application are very valid for use in basic electronics learning for physics student.